PENGEMBANGAN FIKIH SEBAGAI KERANGKA ANALISIS REALITAS SOSIAL KEAGAMAAN DI INDONESIA - Fathorrahman Fathorrahman; Arif Sugitanata; Kunto Dzaki Al Afkari (Studia Sosia Religia, 2026)
This study is motivated by the paradox of socio-religious life in Indonesia, namely the high level of public religiosity that does not always correspond to the quality of social ethics in the public sphere. Religion is strongly present in the forms of ritual, symbolism, identity, and communal expression, yet various problems such as corruption, intolerance, symbolic violence, religious disinformation, and weak social responsibility continue to emerge. Accordingly, this study aims to explain the paradox between the high level of religiosity in Indonesian society and the low quality of social ethics, while also formulating the development of fiqh as an analytical framework expected to bridge the normative dimension of the sharī‘ah and socio-religious reality. This study employs a qualitative approach based on library research by examining relevant literature, with the analysis conducted thematically and conceptually through a deductive reading of normative concepts in Islamic law and an inductive reading of Indonesia’s socio-religious reality. The findings show that the paradox of religiosity cannot be understood merely as an individual moral failure, but rather as a socio-religious phenomenon related to the dominance of legal-formal, textual, and casuistic understandings of fiqh. Under these conditions, fiqh tends to function as a tool for determining legal status, but has not been sufficiently developed as an instrument for reading the social roots of public problems. This study argues that fiqh needs to be reconstructed as a system of knowledge that operates through the dialectical relationship between naṣṣ, ‘aql, and al-wāqi‘. Thus, fiqh functions not only as a tool of social control, but also as a tool of social engineering oriented towards public welfare, justice, and the transformation of social ethics. These findings contribute to the development of Islamic legal studies and socio-religious scholarship by offering a more reflective, critical, contextual, and transformative fiqh framework for reading the realities of Indonesian society.